Preparation of epigallocatechin gallate decorated Au-Ag nano-heterostructures as NIR-sensitive nano-enzymes for the treatment of osteoarthritis through mitochondrial repair and cartilage protection. (May 2022) - Xu, Shibo; Chang, Linna; Zhao, Xingjun; Hu, Yanan; Lin, Yiyi; Chen, Zhenhua; Ren, Xiuli; Mei, Xifan
Abstract: Osteoarthritis (OA), a widespread degenerative disease characterized by cartilage destruction, has emerged as a public health challenge in the current aging society. In addition to applied steroids and surgery, near-infrared (NIR) sensitive nano-enzyme for the treatment of osteoarthritis through mitochondrial repair and cartilage protection is attractive and promising. In this study, a NIR sensitive multifunctional heterostructure (EGCG (Epigallocatechin gallate) decorated Au-Ag nano-jars (E@Au-Ag)) was introduced as an enzyme-sensitive active nanoplatform for the treatment of osteoarthritis. Molecular biology results indicated that E@Au-Ag possesses intrinsic properties of anti-oxidative stress and was able to reduce the apoptosis rate of chondrocytes by 83.3%. The area of the intra-articular joint cavity injected with E@Au-Ag can be elevated to 46.6 °C under NIR to promote the release of EGCG further to induce cartilage regeneration. X-ray radiography and section staining showed that E@Au-Ag reduced cartilage damage and decreased OARSI scores by approximately 52% after 8 weeks of treatment in a surgically induced OA model. The results demonstrated that this multifunctional enzyme-like nanoplatform with a synergistic NIR sensitive property to facilitate cartilage migration and regeneration repair provides a promising OA treatment strategy. Statement of significance: 1. NIR-sensitive nano-enzyme is gaining much attention in the field of biomedical materials. 2. EGCG decorated Au-Ag nano-heterostructures were utilized as NIR-sensitive nano-enzymes for the treatment of osteoarthritis through mitochondrial repair and cartilage protection. 3. The obtained multifunctional Au-Ag nano-heterostructures are promising for osteoarthritis treatment. Graphical abstract: Image, graphical abstract